ZIRCON GEOCHRONOLOGY OF THE ALEKSANDROV METAMORPHIC COMPLEX, SOUTHERN URALS - Krasnobaev A.A.; Cherednichenko N.V. (My University, 2004)
The Aleksandrov Complex (AC) of metamorphic rocks is restricted to the long-lived Zyuratkul Fault on the western slope of the southem Urals, 2-3 km east of the known Taratash Complex. It makes up a NNE-trending tectonic block (1-2.5 × 25 km) among the carbonates of the Lower Riphean Satka Formation The age of the AC remains a most controversial problem